Politeness in Bad Neighbors Movie - Sastika Seli; Dewi Syafitri (Linguistic, English Education and Art (LEEA) Journal, 2018)
The research aims at describing politeness used by Americans in Bad Neighbors movie to express apology. This is a qualitative descriptive research which identified, observed, transcribed the data as well as described them in the sentences. The findings present the strategy of apologizing and the use of address terms overviewed from politeness strategies such as positive politeness, negative politeness and off record. The use of address terms in expressing apology covered terms of addressing in negative politeness includes the use of title plus last name (TLN) (such as Mr. Haywood and Maam) and positive politeness includes different nick names (NN) (such as Mac, Baby, Scoonie, Guys, etc). The variation of apologizing includes direct apology (sorry and I am sorry). In the application of direct apology I am sorry, no address term was used in the expression and it indicates positive politeness. In a direct expression of apology sorry, there was a term of address used preceded the expression and sometimes it also occurred afterward. Based on the description, it can be inferred that most of expression of direct apology expressed in positive politeness because the first speaker wanted to show a more intimate relationship to the second speaker. The position of the terms also affects the purpose and the quality of sincerity of the speakers. This strategy considered to be an effective way to express apology to show that the speaker who committed a responsibility of apologizing regretted the mistakes. Keyword: politeness, apologizing, term of address